(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Always before we start creating or accessing a particular system, it is more than necessary to have a clearer picture of how to create, respectively, how to approach a certain system, in this case of a e-business system. It is much easier as for systems makers, as well as for ordinary users when they have before them a model of how to be accessed in such a system, because such a thing will orient users much easier to purchase products online through various systems on the one hand, but on the other hand it would help makers of systems create much easier such systems when they have already before them the right design. Modeling systems may be done in different ways, depending on the context of its research, but we in this paper we will use UML diagrams for modeling online system where we will make a comparison between UML diagrams and we will present each type of UML diagram in terms of customer access in online systems. Also using predictive techniques as CPM and PERT techniques in the paper we will present the main activities required for access to an online system by different users, and their graphic presentation and critical path finding, which shows the best way to approach such a system. There shall not fail and the description of business models and the introduction of some e-business models that are commonly used in practice in the days of today.